CT-based attenuation correction of whole-body radiotherapy treatment positioning devices in PET/MRI hybrid imaging - Taeubert, Leticia; Berker, Yannick; Beuthien-Baumann, Bettina; Hoffmann, Aswin; Troost, Esther Gera Cornelia; Kachelrieß, Marc; Gillmann, Clarissa (Physics in medicine and biology, 2020)
Objective.To implement computed tomography (CT)-based attenuation maps of radiotherapy (RT) positioning hardware and radiofrequency (RF) coils to enable hybrid positron emission tomography/magnetic resonance imaging (PET/MRI)-based RT treatment planning. Materials and Methods. The RT positioning hardware consisted of a flat RT table overlay, coil holders for abdominal scans, coil holders for head and neck scans and an MRI compatible hip and leg immobilization device. CT images of each hardware element were acquired on a CT scanner. Based on the CT images, attenuation maps of the devices were created. Validation measurements were performed on a PET/MR scanner using a 68Ge phantom (48 MBq, 10 min scan time). Scans with each device in treatment position were performed. Then, reference scans containing only the phantom were taken. The scans were reconstructed online (at the PET/MRI scanner) and offline (via e7tools on a PC) using identical reconstruction parameters. Average reconstructed activity concentrations of the device and reference scans were compared. Results. The device attenuation maps were successfully implemented. The RT positioning devices caused an average decrease of reconstructed PET activity concentration in the range between −8.3 ± 2.1% (mean ± SD) (head and neck coil holder with coils) to −1.0 ± 0.5% (abdominal coil holder). With attenuation correction taking into account RT hardware, these values were reduced to −2.0 ± 1.2% and −0.6 ± 0.5%, respectively. The results of the offline and online reconstructions were nearly identical, with a difference of up to 0.2%. Conclusion. The decrease in reconstructed activity concentration caused by the RT positioning devices is clinically relevant and can successfully be corrected using CT-based attenuation maps. Both the offline and online reconstruction methods are viable options.
Gesehen am 05.01.2021